Green finance instruments and green finance in Uzbekistan (The Peerian Journal, 2022)
The article examines the green instruments, problems and prospects of the green factor of economic growth in Uzbekistan, analyzes the international experience of transition to a green economy, and describes the main directions of development of the green economy in the Republic of Uzbekistan